The Effect of Zigzag Run Training on the Agility of Futsal Extracurricular Students at MAN Insan Cendekia Palu - Saliku, Abdul Gafur; Jumain; Kamarudin; Humaedi (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2025)
This study aimed to examine the effect of zigzag run training on the improvement of agility in students participating in the futsal extracurricular program at MAN Insan Cendekia Palu. The research employed a pretest–posttest experimental design with a total of 20 students, who were divided into control and experimental groups using an ordinal pairing technique. The agility T-test was used as the measurement instrument. The zigzag run intervention was conducted over four weeks with a frequency of three sessions per week. The results indicated that the data were normally distributed, and the Paired Sample t-test for the experimental group yielded a significance value of 0.000, demonstrating a significant improvement in agility following the training. In contrast, the control group showed no significant change. These findings suggest that zigzag run training is effective in enhancing futsal students’ agility and is recommended as a regular component of training programs.